Relationship of Spirituality Leadership Style and SMEs Performance in Halal Supply Chain - Ezanee Mohamed Elias; Siti Norezam Othman; Noorulsadiqin Azbiya Yaacob (International Journal of Supply Chain Management, 2017)
The great influence of consumers' consumption of halal products, mainly food and beverages (FB) have raised new challenges for all manufacturing organisations, specifically the small and medium enterprises. Largely in Malaysia, FB industries are dominated by this scale of enterprises. However, in terms of the halal products manufactured are not produced by those enterprises, but made by large and multinational enterprises. Presently, there is an enormous competition among those enterprises to produce halal products on a large scale all along the supply-chain networks. On the other hand, most of them are stuck to getting halal certificates from the official authority; JAKIM. Besides that, other challenges faced by SMEs that they are deficient of leadership styles, lack of entrepreneurial orientation and inconsistent performance to grasp opportunities existing in the halal markets. Based on previous literatures, these challenges contributed a significant research gap in terms of leaderships in management practice towards the organisation performance. Therefore, this study has constructed a conceptual model based on the leadership theories in which they have a significant impact on an organisation's performance. This paper presents a proposal of a theoretical framework in order to examine the relationship of leadership styles, mainly the spirituality towards the organisation performance which moderates by Shariah based entrepreneurial orientation. All measurements applied in the study are based from the past research. However, some of them are modified suited to the studys objectives. The studys scope is within Malaysian SMEs that involved in the manufacturing of halal FB. Keywords: enterprises, food, halal, leaderships, supply chain